Long-term cardiac follow-up of athletes infected with SARS-CoV-2 after resumption of elite-level sports - van Hattum, J. C.; Daems, J. J.; Verwijs, S. M.; Wismans, L. V.; van Diepen, M. A.; Groenink, M.; Boekholdt, M.; Planken, N.; van Randen, A.; Hirsch, A.; Moen, M. H.; Pinto, Y. M.; et al. (Heart, 2024)
Objective Longitudinal consequences and potential interactions of COVID-19 and elite-level sports and exercise are unclear. Therefore, we determined the long-term detrimental cardiac effects of the interaction between SARS-CoV-2 infection and the highest level of sports and exercise.